Effect of experimental analogs of contingency management treatment on cocaine seeking behavior - Greenwald, Mark K.; Ledgerwood, David M.; Lundahl, Leslie H.; Steinmiller, Caren L. (Drug and alcohol dependence, 2014)
Contingency management (CM) treatment is effective for treating cocaine dependence but further mechanistic studies of its efficacy are warranted. This study aimed to determine whether: (a) higher vs. lower predictable money amounts ($3 vs. $1; analogs of standard voucher-based CM) increase cocaine demand elasticity; and (b) probabilistic amounts matched for expected value with the $3-predictable amount (50% chance of $6; 25% chance of $12; and 12.5% chance of $24; analogs of prize CM) similarly affect cocaine choice. Each of 15 cocaine-dependent participants first completed a qualifying session to ensure that intranasal cocaine functioned as a reinforcer, then completed a 10-session, within-subject, randomized crossover study. During each of the 10 sessions, the participant responded on a progressive ratio schedule to earn units of cocaine (5-mg or 10-mg) and/or money (five monetary conditions above). During the reinforcement qualifying session (10-mg vs. 0-mg units; no money alternative), cocaine choice was high. The $3-predictable amount significantly decreased cocaine choice relative to both the $1-predictable amount and the qualifying session. Cocaine-choices in the probabilistic conditions were similar to the $3 predictable condition. These findings indicate that CM interventions targeted at reducing cocaine self-administration are more likely to succeed with higher value non-drug reinforcement.